Validation of a Questionnaire on COVID-19 Knowledge and Attitude for Dental Patients - Mohammad Reza Khami; Mahsa Karimi; Morenike Oluwatoyin Folayan; Ahmad Reza Shamshiri; Prathip Phantumvanit; Armando E Soto-Rojas; Seyed Hossein Bassir; Heikki Murtomaa (Frontiers in Dentistry)
Objectives: The current study aimed to develop a valid and reliable questionnaire in both English and Persian to assess dental patients' knowledge and attitude during the COVID-19 outbreak.